Quantifying the effect of low-frequency fatigue dynamics on offshore wind turbine foundations: a comparative study - N. Sadeghi; P. D'Antuono; N. Noppe; N. Noppe; K. Robbelein; K. Robbelein; W. Weijtjens; C. Devriendt (Wind Energy Science, 2023)
Offshore wind turbine support structures are fatigue-driven designs subject to a wide variety of cyclic loads from wind, waves, and turbine controls. While most wind turbine loads and metocean data are collected at short-term 10 min intervals, some of the largest fatigue cycles have periods over 1 d. Therefore, these low-frequency fatigue dynamics (LFFDs) are not fully considered when working with the industry-standard short-term window. To recover these LFFDs in the state-of-the-industry practices, the authors implemented a short- to long-term factor applied to the accumulated short-term damages while maintaining the ability to work with the 10 min data. In the current work, we study the LFFD impact on the damage from the fore–aft and side–side bending moments and the sensors' strain measurements and their variability within and across wind farms. While results might vary strongly between sites, for the current site and a stress–life (SN) curve slope of m=5, up to 65 % of damage is directly related to LFFDs.